2003
DOI: 10.1016/s0960-9822(03)00091-5
|View full text |Cite
|
Sign up to set email alerts
|

The ARF-like GTPases Arl1p and Arl3p Act in a Pathway that Interacts with Vesicle-Tethering Factors at the Golgi Apparatus

Abstract: The ARLs are a diverse family of GTPases that are related to ADP-ribosylation factors (ARFs), but whose function is poorly understood. There are at least ten ARLs in humans, two of which have homologs in the yeast Saccharomyces cerevisiae (ARL1/Arl1p and ARFRP1/Arl3p). The function of ARFRP1 is unknown, but mammalian ARL1 has recently been found to interact with a number of effectors including the GRIP domain that is present in a family of Golgi-localized long coiled-coil proteins. We find that in yeast, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
243
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(260 citation statements)
references
References 33 publications
14
243
1
2
Order By: Relevance
“…The two TGN golgins, p230 and golgin-97, depend on Arl1 for membrane recruitment (17)(18)(19)25). Our previous analyses showed that different cargoes are selectively packaged into different Golgi tubules, and that these tubules bud off to form transport carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two TGN golgins, p230 and golgin-97, depend on Arl1 for membrane recruitment (17)(18)(19)25). Our previous analyses showed that different cargoes are selectively packaged into different Golgi tubules, and that these tubules bud off to form transport carriers.…”
Section: Discussionmentioning
confidence: 99%
“…There are four human TGN golgins, namely p230/golgin-245, golgin-97, GCC185 and GCC88 (8)(9)(10)(11)(12)(13), which all belong to a subfamily of golgins characterized by a C-terminal GRIP domain (14)(15)(16). Recruitment of both p230/ golgin-245 (p230) and golgin-97 to the TGN is mediated through an interaction with the small G protein Arl1 (17)(18)(19)(20); however, these two golgins are localized to distinct membrane domains of the TGN (21). Distinct spatial segregation of p230 and golgin-97 is also reflected in their selective function, each being associated with TGN tubules bearing different cargo molecules.…”
mentioning
confidence: 99%
“…GARP interacts directly with small GTPases that localize to the TGN [Ypt6/Rab6 (12, 13) and Arl1 (14)], and in humans, GARP also interacts with SNARE proteins specific to the retrograde pathway (t-SNARE proteins syntaxin 6, syntaxin 16, and v-SNARE Vamp4) and may facilitate formation of the SNARE complex (2) at the TGN, the site of vesicle fusion. The SNARE interaction requires N-terminal regions in the Vps53 and Vps54 proteins (2).…”
mentioning
confidence: 99%
“…The transport was restored to almost complete level (96%) (lane 3) when the same amount of GST-GRIP was heat-denatured before addition, suggesting that the inhibition requires the intact conformation of the GRIP domain. When the conserved residue Y697, which is essential for interaction with Arl1 and for Golgi targeting (Barr, 1999;Kjer-Nielsen et al, 1999a;Munro and Nichols, 1999;Lu and Hong, 2003;Panic et al, 2003b), was mutated to Ala, the resultant fusion protein, GST-GRIP/Y697A (lane 5), exhibited little inhibition toward STxB transport relative to the control (lane 4). Furthermore, with increasing amounts of GST-GRIP added to the assay, the transport of STxB was correspondingly reduced to a plateau of ϳ20% ( Figure 1C), indicating that the inhibition is dose dependent.…”
mentioning
confidence: 99%